2012
DOI: 10.1371/journal.pone.0038120
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Aggressive Behavior from the Giant Coral Reef Fish, Bolbometopon muricatum, in a Remote Marine Reserve

Abstract: Human impacts to terrestrial and marine communities are widespread and typically begin with the local extirpation of large-bodied animals. In the marine environment, few pristine areas relatively free of human impact remain to provide baselines of ecosystem function and goals for restoration efforts. Recent comparisons of remote and/or protected coral reefs versus impacted sites suggest remote systems are dominated by apex predators, yet in these systems the ecological role of non-predatory, large-bodied, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…This case of sexual dimorphism in cranial osteology is also similar to the rare cases found in extant teleosts today such as Kurtus gulliveri (Berra and Humphrey, 2002), Danionella dracula (Britz et al 2009), Bolbometopon muricatum (Muñoz et al, 2012) and Coryphaena hippurus (Schuck, 1951). This finding indicates that sexual dimorphism may be especially pronounced in pycnodonts and may reveal that similar taxa currently classified as distinct species may be sexual dimorphs of one another.…”
Section: Discussionsupporting
confidence: 81%
“…This case of sexual dimorphism in cranial osteology is also similar to the rare cases found in extant teleosts today such as Kurtus gulliveri (Berra and Humphrey, 2002), Danionella dracula (Britz et al 2009), Bolbometopon muricatum (Muñoz et al, 2012) and Coryphaena hippurus (Schuck, 1951). This finding indicates that sexual dimorphism may be especially pronounced in pycnodonts and may reveal that similar taxa currently classified as distinct species may be sexual dimorphs of one another.…”
Section: Discussionsupporting
confidence: 81%
“…In those cases, some morphological female fish may be males that have not yet developed the male forehead morphology. In our study, all observations of courtship and spawning that we observed were between dimorphic fish, presumably female and male Suzuki et al, 2008;Muñoz et al, 2012).…”
Section: Video Analysessupporting
confidence: 50%
“…The pair then slowly ascended to one meter below the water's surface, releasing a clearly visible gamete cloud, followed by a slow descent back to the school. Muñoz et al (2012) first documented ritualized head-butting behavior of Bolbometopon associated with earlymorning spawning events of an unexploited and intact population at Wake Atoll, and suggested PeerJ reviewing PDF | (v2014:09:2680:1:0:NEW 4 Nov 2014)…”
Section: Reviewing Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extent of the aggregation and the apparent ephemeral nature of temporary dichromatism, it was difficult to ascertain numbers of males and females. No clear evidence of territoriality or aggressive interactions such as male–male chases (Muñoz et al, ) or head butting (Muñoz et al, ) were observed during the main aggregation or on review of video footage.…”
Section: Summary Of Key Differences In Spawning Aggregation Size and mentioning
confidence: 99%